PENGARUH DISIPLIN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DENGAN MODERASI LINGKUNGAN SEKOLAH - Rahayu, Rika; Gumilar, Rendra; Aisyah, Iis (HATTA : Jurnal Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
The problem in this study is the low learning outcomes of students. The purpose is to examine the factors influencing students' low learning outcomes in economics subjects by analys several contributing factors, namely internal factors of learning discipline and external factors of the school environment, which act as moderating variables. The research method used is quantitative, with questionnaires as the data collection technique. The population in this study consists of Grade X and XI students at SMA Negeri 1 Jatiwaras who study Economics, and the sample comprises 251 students selected using Probability Sampling with proportionate stratified random sampling techniques. The research results indicate a significant influence of learning discipline on learning outcomes, as well as the impact of the school environment on learning outcomes. Furthermore, the school environment moderates the influence of learning discipline on learning outcomes. These findings confirm that both research hypotheses are accepted.